Multilevel Analysis of Dengue Hemorrhagic Fever in Bantul Regency - Nurkhairani, Nurkhairani; Rahardjo, Setyo Sri; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Dengue Hemorrhagic Fever (DHF) is one of the main vector-borne diseases infecting humans. It remains a major public health problem in tropical and sub-tropical regions around the world. The poor physical and social environment are the leading cause of the increasing incidence of DHF. This study aimed to determine the effect of the physical and social environment on dengue incidence using multilevel analysis.Subjects and Method: This was an analytic a case-control study conducted in Bantul, Yogya